DCAF4, a novel gene associated with leucocyte telomere length. Issue 3 (26th January 2015) - Mangino, Massimo; Christiansen, Lene; Stone, Rivka; Hunt, Steven C; Horvath, Kent; Eisenberg, Dan T A; Kimura, Masayuki; Petersen, Inge; Kark, Jeremy D; Herbig, Utz; Reiner, Alex P; Benetos, Athanase; et al.
Abstract : Background: Leucocyte telomere length (LTL), which is fashioned by multiple genes, has been linked to a host of human diseases, including sporadic melanoma. A number of genes associated with LTL have already been identified through genome-wide association studies. The main aim of this study was to establish whether DCAF4 (DDB1 and CUL4-associated factor 4) is associated with LTL. In addition, using ingenuity pathway analysis (IPA), we examined whether LTL-associated genes in the general population might partially explain the inherently longer LTL in patients with sporadic melanoma, the risk for which is increased with ultraviolet radiation (UVR). Results: Genome-wide association (GWA) meta-analysis and de novo genotyping of 20 022 individuals revealed a novel association (p=6.4×10 −10 ) between LTL and rs2535913, which lies within DCAF4 . Notably, eQTL analysis showed that rs2535913 is associated with decline in DCAF4 expressions in both lymphoblastoid cells and sun-exposed skin (p=4.1×10 −3 and 2×10 −3, respectively). Moreover, IPA revealed that LTL-associated genes, derived from GWA meta-analysis (N=9190), are over-represented among genes engaged in melanoma pathways. Meeting increasingly stringent p value thresholds (p<0.05, <0.01, <0.005, <0.001) in the LTL-GWA meta-analysis, these genes were jointly over-represented for melanoma at p values ranging from 1.97×10 −169 to 3.42×10 −24 . Conclusions: We uncovered a new locus associated with LTL in the general population. We also provided preliminary findings that suggest a link of LTL through genetic mechanisms with UVR and melanoma in the general population.